A reusable robust radio frequency biosensor using microwave resonator by integrated passive device technology for quantitative detection of glucose level - Kim, N.Y.; Dhakal, R.; Adhikari, K.K.; Kim, E.S.; Wang, C. (Biosensors & bioelectronics, 2015)
A reusable robust radio frequency (RF) biosensor with a rectangular meandered line (RML) resonator on a gallium arsenide substrate by integrated passive device (IPD) technology was designed, fabricated and tested to enable the real-time identification of the glucose level in human serum. The air-bridge structure fabricated by an IPD technology was applied to the RML resonator to improve its sensitivity by increasing the magnitude of the return loss (S21). The resonance behaviour, based on S21 characteristics of the biosensor, was analysed at 9.20 GHz with human serum containing different glucose concentration ranging from 148-268 mg dl(-1), 105-225 mg dl(-1) and at a deionised (D) water glucose concentration in the range of 25- 500 mg dl(-1) for seven different samples. A calibration analysis was performed for the human serum from two different subjects and for D-glucose at a response time of 60 s; the reproducibility, the minimum shift in resonance frequency and the long-term stability of the signal were investigated. The feature characteristics based on the resonance concept after the use of serum as an analyte are modelled as an inductor, capacitor and resistor. The findings support the development of resonance-based sensing with an excellent sensitivity of 1.08 MHz per 1 mg dl(-1), a detection limit of 8.01 mg dl(-1), and a limit of quantisation of 24.30 mg dl(-1).